A Checklist of Iranian Cockroaches (Blattodea) with Description of Polyphaga sp as a New Species in Iran - SaedehSadat Hashemi-Aghdam (Journal of Arthropod-Borne Diseases, 2015)
Background: Cockroaches are of vital importance medically and hygienically. They are able to contaminate foods and act as vectors of pathogenic agents such as bacteria, protozoa, and parasites to human environment either mechanically or through their digestive system. Cockroaches belong to the phylum Arthropoda, class Insecta, and order Blattodea or Blattaria. To date, over 4,500 cockroach species have been reported from different parts of the world. We overviewed the documents involved Iranian cockroaches to up-to-date checklist of cockroach species distributed in various provinces of Iran. Methods: An extensive literature review was performed in 2013 on Iranian handbooks, reports and published data available since 1986 to obtain a comprehensive list of Iranian cockroaches. Furthermore, in an entomological survey in Tehran, cockroach specimens were collected and identified based on morphological and the DNA sequences of the mitochondrial cytochrome oxidase subunit II (COII) gene (mt-DNA COII) characteristics. Results: Morphological characterization revealed presence of an un-described species very similar to Polyphaga aegyptiaca, P. indica and somehow to Pycnoscelus surinamensis, however, supplementary molecular analysis revealed the species was associated with Polyphaga of Corydiidae (Polyphagidae). With regards to the report of the un-described species, the cockroach fauna of Iran includes three families, 14 genera, and 26 species. Conclusion: Some species has not been collected or reported recently and also many geographical regions of the country have not been studied yet, hence a systematic research is required to reveal the real cockroach list of the country. Geographical distributions, nomination changes, and synonyms of cockroach species are presented.